Perlindungan Harimau Sumatera Menurut Convention On International Trade In Endangered Species Of Wild Fauna And Flora (Cites) 1963 - Mainuru, Muhammad Zidhan L; Rehatta, Veriana Josepha Batseba; Daties, Dyah Ridhul Airin (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: The illegal trade in protected animals is increasing in places where laws are not respected, as if they weren't there. This is reflected in the decrease in the number of wildlife and the increase in the number of legal and illegal wildlife traders whose criminals do not face severe sanctions. The number of Sumatran tigers is decreasing, reaching around 400 individuals. In various parts of Sumatra, these endangered and protected animals continue to be hunted and traded for their organs. Apparently, in the near future, they succeeded in capturing or blocking the Medan tiger skin trade.Purposes of the Research: This writing aims to know and understand the Regulations regarding the protection of endangered species based on the 1963 Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) and the Implementation of CITES 1963 in Indonesia to protect the Sumatran Tiger.Methods of the Research: Normative research method with the type of research is qualitative analysis. The problem approach used is the statute approach, the conceptual approach and the case approach. The sources of legal materials used are Primary legal materials, Secondary legal materials, and Tertiary legal materials and are used as a technique for collecting legal materials, then processing and analyzing legal materials through methods of interpretation, harmonization, systematic and legal discovery.Results of the Research: The results of the study show that the arrangements regarding the protection of endangered species based on the 1963 Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) are that as a whole, CITES is a convention that applies as a general guide to regulate matters relating to trade of all kinds. Wild plants and animals that live in nature. Specifically regarding the protection of Sumatran tigers as implementation of CITES 1963 is the enactment of Presidential Decree No. 43 of 1978 concerning Ratifying the Convention On International Trade in Endangered Species of Wild Fauna and Flora, Law No. 5 of 1990 concerning Conservation of Natural Resources, Biology and Their Ecosystems, Regulations Government Number 8 of 1999 Utilization of Wild Plants and Animals, Minister of Forestry Regulation Number P.42/Menhut-II/2007 concerning Sumatran Tiger Conservation Plans and Actions.